Pengelompokan Sarana Prasarana Sekolah Dasar Kabupaten/Kota Di Indonesia Menggunakan Algoritma K-Means Clustering - OK Muhammad Zikri Fadillah; Abdul Halim Hasugian (Universitas Budi Luhur, 2026)
Equitable access to quality basic education remains a national priority in Indonesia, yet the condition of elementary school facilities and infrastructure still varies considerably across regions. This research applies the K-Means Clustering algorithm to classify the condition of elementary school facilities and infrastructure at the regency/city level in Indonesia, addressing disparities in basic education facilities through a more objective, data-based mapping approach. Data were obtained from the 2025 Data Portal of the Ministry of Primary and Secondary Education, covering 514 regencies/cities and six indicators: classrooms, libraries, laboratories, school health units, boys’ toilets, and girls’ toilets. Each indicator was converted into a numerical score based on four condition categories and normalized using Min-Max Normalization prior to clustering. The number of clusters was determined using the Elbow Method and validated using the Davies-Bouldin Index, both supporting K=3. The clustering grouped the 514 regencies/cities into 117 regions with relatively low facility conditions, 302 with relatively moderate conditions, and 95 with relatively high conditions, with the low cluster concentrated in eastern Indonesia, particularly Papua and Maluku. The main contribution of this research is a data-driven cluster map that education authorities can use as an evidence-based reference for prioritizing budget allocation and infrastructure development toward regencies/cities in the low cluster, as well as a replicable scoring-normalization-clustering pipeline adaptable for future studies with additional indicators.